Biomass to energy: mass and exergy assessment of carbon mitigation and triple bottom line assessment - Veiga, João Paulo Soto (2016)
Earth is exposed to an amount of energy that is fixed organically via photosynthesis and stored as fossil fuels, which are currently the major energy sources of humanity. Since Arrhenius concluded that carbon dioxide emissions from fossil fuels could lead to a climate warming, studies have sought ways to reduce human contribution on the environment to mitigate possible negative impacts on climate. The increasing world population is an obstacle for the efforts to reduce CO2 emissions and other greenhouse gases (GHG), because it demands more energy for transportation, electricity and heating. Among several renewable energy sources, biomass for fuels stands out, such as sugarcane ethanol in Brazil. Using biomass for fuels may help reducing the pressure on fossil fuels, besides, fixing organic carbon already emitted, contributing to mitigate problems of climate change and global warming. Thus, this study aims to analyse carbon cycles of mitigating emissions from fossil fuels with biofuel based on useful energy (exergy) content to determine the equivalent area required. Previous studies of life cycle assessment in sugarcane and eucalyptus were used to obtain carbon- and energy-flow data. These data were applied to estimate the available exergy to the final user through different routes of biofuel production, including current and evolving technologies. Exergy assessment demonstrated that on average, each Mg of biomass produced, led to a change of 3.02 GJ on sugarcane scenarios and 5.93 GJ on eucalyptus scenarios. Reducing sugarcane straw moisture from 50% to 30% increased the exergy output in 13.32 GJ ha-1, an increase of 0.67 GJ ha-1 for each 1% of moisture reduce. Eucalyptus to firewood, reducing moisture from 20% to 15% had an increase of 7.52 GJ ha-1 in the exergy output, representing 1.50 GJ ha-1 of increase for each 1%. This kind of assessment brings a new point of view in carbon mitigation, looking for its functionality. Biofuel use implications in environmental, social and economic aspects were also studied through a hybrid input-output life cycle assessment (IO-LCA) showing differences between the occupation of land use and two different ways of sugarcane production. The IO-LCA showed, in areas of land use change from pasture to sugarcane, energy consumption is increased by 3.7 times, employment is reduced by 5.4 times, and GHG emissions are reduced to only 2% of original emissions for each unit of R$ of final demand changed Most of the employment is generated by the sugarcane supply chain sector. Comparing sugarcane produced by the mills, it originates more direct full time jobs and probably in a more formal job market than sugarcane produced by farm suppliers. Farm suppliers use less energy and release less GHG than mills sugarcane production.